2020
DOI: 10.1016/j.erss.2019.101329
|View full text |Cite
|
Sign up to set email alerts
|

Happier with less? Members of European environmental grassroots initiatives reconcile lower carbon footprints with higher life satisfaction and income increases

Abstract: Scientists and policymakers recognize the need to address consumption and lifestyles in order to reconcile environmental and development agendas. Sustainability-oriented grassroots initiatives emerge bottom-up to create opportunities for sustainable lifestyles; yet no prior assessment has ascertained the efficacy of their members to reduce carbon footprints (CF) and enhance well-being. We compare the CF of non-members and members of grassroots initiatives in the domains of food, clothing, housing and transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 74 publications
(232 reference statements)
2
52
0
1
Order By: Relevance
“…Income situation is one of the most important factors affecting consumer life satisfaction in microeconomic variables. Vita et al [27] compared the various household groups by testing the influence of socio-economic variables that were typically associated with consumer life satisfaction and suggested that the positive influence of income was verified. In general, income is positively correlated with consumer life satisfaction.…”
Section: Previous Research On Consumer Life Satisfactionmentioning
confidence: 99%
“…Income situation is one of the most important factors affecting consumer life satisfaction in microeconomic variables. Vita et al [27] compared the various household groups by testing the influence of socio-economic variables that were typically associated with consumer life satisfaction and suggested that the positive influence of income was verified. In general, income is positively correlated with consumer life satisfaction.…”
Section: Previous Research On Consumer Life Satisfactionmentioning
confidence: 99%
“…People's attachment plays a crucial role in their subjective well-being in terms of sustainability initiatives [35,36], information technology [37], and adult attachment styles [38,39]. Yet, despite its significance, research on the relationship between attachment and subjective well-being has not been undertaken in SDG crowdfunding settings.…”
Section: Introductionmentioning
confidence: 99%
“…Despite declining carbon intensities, we cannot conclude that the NAFTA launched Mexico towards sustainability as we only find indication of relative decoupling of decelerating growth in emissions with respect to growth in GDP. A critique of carbon intensity as indicator for decoupling is the role of ballooning financial, services, and trade -all of them relatively immaterial sectors that inflate GDP and thus make the indicator unsuitable for confirming relative decoupling [21], [22]. Moreover, the increases in eco-efficiency are typically overwhelmed by the total volume increase in footprints i.e.…”
Section: Discussionmentioning
confidence: 99%